The proof uses logarithmic differentiation and geometric series expansion only. zn−1f′(1z)znf(1z)=1z(logf)′(1z)=1z∑11z−xi=∑11−xiz=∑xkizk=∑σkzk=Nf(z) For example suppose f=(z−x0)(z−x1)=(z−2)(z−3)=z2−5z+6. The first few sums are σ0=2,σ1=5,σ2=13,σ3=35,σ4=97 so Nf≈2+5z+13z2+35z3+97z4. Furthermore znf(1z)=1−5z+6z2 and zn−1f′(1z)=2−5z. We may test (1) by computing its left- and right-hand sides up to fourth order: (2+5z+13z^2+35z^3+97z^4)(1-5z+6z^2) = (2-5z) \mod z^5. Conversely, we can compute more terms \sigma_k by polynomial division: N_f = \frac{2-5z}{1-5z+6z^2} = \sum_{0\leq k\lt m}\sigma_kz^k + z^m\frac{\textrm{remainder polynomial}}{1-5z+6z^2} In python:
>>> z = sympy.var('z') >>> Nf = sympy.fps((2-5*z)/(1-5*z+6*z*z)) >>> Nf.truncate(10) 2 + 5*z + 13*z**2 + 35*z**3 + 97*z**4 + 275*z**5 + 793*z**6 + 2315*z**7 + 6817*z**8 + 20195*z**9 + O(z**10)